Store Brands: Who Buys Them and What Happens to Retail Prices When They Are Introduced? - Bonfrer, Andre (Institutional Knowledge at Singapore Management University, 2003)
In this paper we study store brand demand behavior by examining a panel of household level and store-level data in five stores located in a competing market area. We seek to address three fundamental questions from this data. First, is there a link between store loyalty and brand loyalty? Second, does store loyalty raise store brand choice probabilities? Third, if a store brand is introduced into a category, what happens to the retail prices of the incumbent brands in the category? We find that store loyalty is negatively associated with brand loyalty, and that store loyalty increases the likelihood of a store brand purchase in a given category. We find mixed evidence on how the retailer changes prices of incumbent brands when it introduces a store brand to the category. Category level market structure measures are used to help identify under what conditions the category prices fall or rise. A number of robustness checks are used to help validate our findings.